Effect of CYP3A4 inhibitor and induction on the pharmacokinetics and safety of FHND9041, a novel EGFR T790M inhibitor, in healthy Chinese - Chang Lu; Dongmei Cheng; Yunqiu Xie; Minghong Shang; Rongzhen Chen; Yongqiang Zhu; Jian Gong; Huan Zhou (BMC Pharmacology and Toxicology)
Abstract Background Non-small cell carcinoma is the main pathologic type of lung cancer, and a large number of clinical trials have shown that epidermal growth factor receptor tyrosinase inhibitors exhibit superior clinical efficacy and lower toxicity compared with chemotherapy. FHND9041 is a new irreversible EGFR T790M mutation-selective small molecule kinase inhibitor, a third-generation EGFR inhibitor developed by Nanjing Chuangte Pharmaceutical Technology Co., Ltd. The aim of this study was to evaluate the effects of oral Itraconazole capsules and oral Rifampicin capsules on the pharmacokinetic profile and safety and tolerability of a single oral dose of FHND9041 capsules in healthy Chinese male subjects. Patients and methods This study employed a single-center, open-label, fixed-sequence design, comprising two parallel groups: Group 1 received FHND9041 40 mg in combination with Itraconazole, while Group 2 received Rifampicin in combination with FHND9041 80 mg. Each group enrolled 16 subjects for a two-period study, with the first period involving monotherapy and the second period involving co-administration. All subjects participating in this clinical trial were healthy adult Chinese males. Results In healthy subjects, after a single oral administration of 40 mg FHND9041 capsules, the corrected geometric mean ratios (90% confidence intervals) of FHND9041 Cmax, AUC0 − last, and AUC0 − inf when co-administered with itraconazole capsules compared to the monotherapy phase were 111.46% (103.26 − 120.30%), 169.53% (156.21 − 183.99%), and 168.25% (156.26 − 181.15%), respectively. The 90% confidence interval for Cmax fell within the 80-125% range, while the 90% confidence intervals for both AUC0 − last and AUC0 − inf exceeded the 80-125% range. Following a single oral dose of 80 mg FHND9041 capsules, the adjusted geometric mean ratios (90% confidence intervals) of Cmax, AUC0 − last, and AUC0 − inf for FHND9041 during co-administration with Rifampicin compared to monotherapy were 52.12% (41.95 − 64.74%), 16.47% (13.34 − 20.31%), and 16.51% (13.56 − 20.09%), respectively. The 90% confidence intervals for Cmax, AUC0 − last, and AUC0 − inf all fell outside the 80 − 125% range. No serious adverse events occurred during the trial. Conclusions Co-administration with Rifampicin significantly reduced the exposure of FHND9041. Therefore, it is recommended to avoid co-administration of FHND9041 with Rifampicin and other potent CYP3A4 inducers. Conversely, co-administration with Itraconazole significantly increased the total exposure of FHND9041. Caution is advised when FHND9041 is co-administered with Itraconazole or other strong CYP3A4 inhibitors. Close monitoring of tolerability during co-administration is essential, and dose reduction may be necessary if required. FHND9041 capsules demonstrated good safety and tolerability when used alone or in combination with strong CYP3A4 inhibitors or inducers. Trial registration Registered 03/27/2023 ( http://www.chinadrugtrials.org.cn/index.html , CTR202300931).